Pengaruh Pengetahuan Akuntansi, Kecerdasan Emosional, Religiusitas, Penghargaan Finansial dan Pertimbangan Pasar Kerja Terhadap Minat Berkarir Sebagai Akuntan Publik - Siti Nurbuana Dewi; Dyah Pravitasari (ITB AAS INDONESIA Surakarta, 2022)
The accuracy of determining and choosing a career is an important point in human life, in-depth knowledge of a career must be applied, such as providing understanding for prospective workforce. One of the candidates for the workforce is economics graduates, including those from the Islamic accounting department. The object in this research was Islamic accounting student of UIN Sayyid Ali Rahmatullah Tulungagung. This study aims to examine the effect of accounting knowledge, emotional intelligence, religiosity, financial rewards and labor market considerations on interest in a career as a public accountant in Islamic accounting students at UIN Sayyid Ali Rahmatullah Tulungagung. The research method used is multiple linear regression. The results showed that accounting knowledge and emotional intelligence had no significant effect, while religiosity, financial rewards and labor market considerations had a significant effect on career interest as a public accountant in Islamic accounting students at UIN Sayyid Ali Rahmatullah Tulungagung.